2005
DOI: 10.1007/s10552-004-5519-6
|View full text |Cite
|
Sign up to set email alerts
|

Two large prospective studies of mortality among men who use snuff or chewing tobacco (United States)

Abstract: These two prospective studies provide limited evidence that current use of chewing tobacco or snuff may increase mortality from heart disease and stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
185
3
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(197 citation statements)
references
References 26 publications
7
185
3
2
Order By: Relevance
“…40 The mechanisms, including the possibility of confounding, are yet to be established. The effect-modification by attained age might suggest that at least 60 years of exposure is required for the effect.…”
Section: Discussionmentioning
confidence: 99%
“…40 The mechanisms, including the possibility of confounding, are yet to be established. The effect-modification by attained age might suggest that at least 60 years of exposure is required for the effect.…”
Section: Discussionmentioning
confidence: 99%
“…ST use in the U.S. has been associated with periodontal disease (Ernster et al, 1990;Fisher, Taylor, & Tilashalski, 2005) and precancerous oral lesions (Mattson & Winn, 1989). ST use has also been associated with oral and extra-oral cancer (Goodman, Morgenstern, & Wynder, 1986;Henley, Thun, Connell, & Calle, 2005;Muscat, Hoffmann, & Wynder, 1995;Stockwell & Lyman, 1986) as well as cardiovascular and cerebrovascular disease (Henley et al, 2005;Teo et al, 2006). Evidence also suggests that smokeless tobacco may be a gateway drug for smoking initiation in adolescent and young adult males (Haddock et al, 2001;Severson, Forester, & Biglan, in press;Tomar, 2003a), although conflicting results have been reported in other studies (O'Connor, Kozlowski, Flaherty, & Edwards, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Male users of smokeless or chewing tobacco have also been shown in US prospective studies to have higher death rates from all causes compared with non-users (CPS-I and II studies) and also higher death rates from cancer of the gastrointestinal tract overall (CPS-I study), but separate data on the upper gastrointestinal tract were not shown [13].…”
mentioning
confidence: 99%